2017
DOI: 10.1016/j.medici.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Unscheduled return visits to a pediatric emergency department

Abstract: RVs accounted for only a small proportion of visits to the ED. RVs were more prevalent among younger patients and patients with a GP referral as well as performed more often after discharging from the ED in the evening and at night.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…We reviewed and analyzed both their demographic characteristics and clinical outcomes and compared them with those admitted to the ICU on initial visits. A previous nationwide-based study in the U.S. from 2012 showed that 698,000 pediatric ED revisits (2.7%) were documented over 7 years [17, 18]. In that study, among all PED revisit patients, the ICU admission rate was about 16.7 per 100,000 PED discharges.…”
Section: Discussionmentioning
confidence: 89%
“…We reviewed and analyzed both their demographic characteristics and clinical outcomes and compared them with those admitted to the ICU on initial visits. A previous nationwide-based study in the U.S. from 2012 showed that 698,000 pediatric ED revisits (2.7%) were documented over 7 years [17, 18]. In that study, among all PED revisit patients, the ICU admission rate was about 16.7 per 100,000 PED discharges.…”
Section: Discussionmentioning
confidence: 89%
“…To minimize the likelihood of capturing revisits unrelated to the initial visit complaint, a 72 h window for revisit was used. 29,31,33,34,38,44 All patients with at least one revisit to the ED within 72 h of discharge from their index visit were categorized as having a revisit. If patients had more than one revisit within the 72 h period after an index visit, we only considered the first revisit in the analysis.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…24,25 ED revisits resulting in hospitalization are not necessarily associated with poorer quality care or medical errors [26][27][28] ; however, revisits overall may be associated with crowding, higher medical costs, and lower patient/family satisfaction. 24,[29][30][31][32] Pediatric ED return visits are widely studied, 26,27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] but few studies examining revisit predictors include language as a factor. 13,14,39 A better understanding of the impact of language on pediatric care quality and outcomes 3 and improved solutions to address these disparities are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, our observed frequency of ED return visits was low, and we found no statistically significant difference between the two study groups (2.8% among pathway adherent versus 0.9% among pathway deviant, P=0.14). Previously reported general RTED rates ranges from 3 to 8.7% (15)(16)(17)(18)(19) and 4.1% in an asthma specific population (20). The discrepancy between our findings and prior studies may be related to the time frame applied to the returns: most studies report returns within 48 hours to 7 days as opposed to the 24 hours time frame used in our study.…”
Section: Discussionmentioning
confidence: 99%